Problem of applying the law on positivist grounds, judge's dilemmas, judicial paradoxes. - Lemańska, Joanna (PRAWO i WIĘŹ, 2020)
The paper tackles contemporary problems of law application which can be identified in the area of legal positivism, e.g. moral evaluation of the law in the course of judicial interpretation or degree of free evaluation of positive law by a judge in the context of law enforcement criteria. In the culture of statutory law, it is stressed that processes of law making and law applying must be separated. At the same time, a judge should be characterized by moderation in terms of interpretation and decision-making. The author attempts to combine the extreme approaches resulting from these different paradigms: the one perceiving a judge as a „mouth of an act” and the other involving a non-positivist postulate of quasi-creation of law meaning through a free  econstruction of norms from laws.